Aksjologia i prawo przekształceń własnościowych w gospodarce - Powałowski, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The possessional transformations have mainly subjective character, depending first of all on “replacing” the definite subjects of right of property by other subjects. The forms of possessional transformations are nationalization and its consequences, and so to say reverse: reprivatization, affranchisement, municipalisation and privatization. Each of these forms is connected with undertaking legal and actual actions, the aim of which is the induction of suitable change of subject of the property right. The basis of these actions are acts of law with legal ranks introducing the obligation — being actualized in the course of a suitable procedure — taking over of the property right from the existing owner owners. In each case of performing the possessional transformation, formulated — in clear way or inferred — the premise or the aim of transformation, in peculiarity is then the public business which is given diverse content and the meaning. Not only however generally comprehended and not always identified public business is the premise of making of possessional transformations. The basis of those transformations are different kind of values of the character both legal and economic as well as social and as a consequence there were and still are different motives premise of their making.
Keywords: possessional transformation; nationalization; reprivatization; municipalization; franchisement; privatization; public business